Modified NASICON structure vanadium phosphate salt composite material and preparation method and application thereof
Through wet reaction and carbon composite technology, a modified NASICON structural vanadium phosphate composite material was prepared, which solved the problems of uneven carbon coating, low conductivity and irregular morphology of existing materials during the preparation process, and achieved high electrochemical performance and good processing performance of the material. It was suitable for the positive electrode materials of secondary batteries.
Patent Information
- Application Number
- CN202411955673.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-28
- Publication Date
- 2025-04-15
AI Technical Summary
The existing NASICON structural vanadium phosphate salt materials have problems such as uneven carbon coating, low conductivity and irregular material morphology during the preparation process, which limits their application in secondary batteries.
The amorphous porous preproduct was prepared by wet reaction method, and the carbon layer was modified by wet grinding and the addition of secondary carbon composite raw materials, and finally the modified NASICON structural vanadium phosphate composite material was obtained by high-temperature calcination.
It realizes the material's morphology, large powder density, small specific surface area and low powder resistivity, and improves the electrochemical and processing properties of the material, and is suitable for the positive electrode materials of secondary batteries.
Smart Images

Figure CN119833600A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of secondary battery positive electrode materials, and in particular to a modified NASICON structure vanadium phosphate composite material, a preparation method and use thereof. Background Art
[0002] Among the positive electrode materials of secondary batteries, polyanionic compounds, vanadium phosphates, are a class of materials with a typical sodium superionic conductor structure (NASICON), which have high ion diffusion coefficients and stable three-dimensional skeleton structures, and small volume expansion coefficients during ion insertion / extraction. Representative materials such as Na3V2(PO4)3 (abbreviated as NVP) and Li3V2(PO4)3 (abbreviated as LVP) have the advantages of high charge and discharge voltage, large energy storage capacity, fast charge and discharge capability and good cycle stability. Therefore, they are an important class of secondary battery materials and have attracted much attention. Although vanadium phosphate materials have good application prospects in theory, their low electronic conductivity severely limits the material's ion storage properties, so they have poor rate performance and long cycle performance, and are subject to certain limitations whether used as secondary battery positive or negative electrodes.
[0003] At present, the methods for improving the performance of NA3V2(PO4)3 materials mainly include material nano-sizing, carbon coating and ion doping. Material nano-sizing shortens the distance of ion diffusion and electron transmission, and improves the electrochemical performance of the material to a certain extent. However, material nano-sizing will reduce the volume energy density of the material, and nano-materials are easy to agglomerate during preparation and use, and make the material processing difficult, which is not conducive to large-scale industrial application. Surface carbon coating can improve the electronic conductivity of the material, but because the surface coating is carried out by pyrolysis of organic carbon source, the carbon is usually a loose and porous structure. On the one hand, it cannot effectively prevent the side reaction between the positive electrode material and the electrolyte and the dissolution of vanadium ions. On the other hand, it will also cause the material specific surface area to be too large and the material density to decrease significantly. Ion doping can improve the intrinsic ionic conductivity and electronic conductivity of the material or stabilize the crystal structure to a certain extent, but the modification effect of ion doping alone is limited. In this material electrochemical reaction system, inert metal ions doping at the V position (such as Al, Ti, Mg, etc.) will lead to a significant decrease in the capacity of the material, and active metal ion doping (such as Cr, Fe, Mn, etc.) often causes the material to have problems such as accelerated cycle attenuation.
[0004] Conventional preparation of NA3V2(PO4)3 carbon composite materials usually adopts a single sol-gel method, hydrothermal method, solid phase method, etc. for synthesis, so that the prepared materials cannot have both good material processing performance and excellent electrochemical performance. Excellent material processing performance usually requires a low specific surface area, a reasonable particle size distribution, a high tap density and as little residual alkalinity as possible. However, the materials prepared by the sol-gel method and the hydrothermal method often have very small primary particle sizes, or their morphology is special (such as petal-shaped, lamellar structure, etc.) resulting in a large specific surface area of the material. Although the solid phase method is simple to operate, the prepared material particles are large, the single component distribution is uneven, and the cycle stability and rate performance are poor. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a modified NASICON structure vanadium phosphate composite material, aiming at the problems that the existing NASICON structure vanadium phosphate material preparation method has carbon coating defects, poor conductivity and irregular material morphology and particle size to varying degrees. The method has simple steps, is easy to implement, and can ensure the consistency of materials in a continuous production process. The prepared composite material has the advantages of regular morphology, high powder density, small specific surface area and low powder resistivity, and has excellent electrochemical properties and battery processing performance.
[0006] It should be noted that, in the present invention, unless otherwise specified, the specific meaning of "including" in relation to composition limitations and descriptions includes both open-ended "including", "comprising", etc. and similar meanings, as well as closed-ended "composed of", "composed of", etc. and similar meanings.
[0007] To achieve the above object, the technical solution adopted by the present invention is: a method for preparing a modified NASICON structure vanadium phosphate composite material, comprising the following steps:
[0008] Step 1, adding a vanadium source and a carbon source into water under stirring conditions, then raising the temperature of the solution to 85°C-95°C, adding a phosphorus source, and continuously stirring for 10-30 minutes for wet reaction to obtain a suspension;
[0009] Step 2: According to the molecular formula Li x Na 3-x V2(PO4)3, wherein 0≤x≤3, (preferably 2.5≤x≤3), add a lithium source and / or a sodium source under stirring conditions, react at 85-98°C for 10-60min, the solution gradually becomes viscous to a gel solid state, and the precursor is obtained after drying and grinding;
[0010] Step 3, calcining the precursor under an inert atmosphere (low temperature calcination) to obtain an amorphous porous pre-product;
[0011] Step 4, wet grinding the amorphous porous pre-product, adding a secondary carbon composite raw material during the wet grinding process to obtain a uniform mixture;
[0012] Step 5: Dry the mixture, and calcine (high temperature calcination) to obtain a modified NASICON structure vanadium phosphate composite material.
[0013] Furthermore, in step 1, a vanadium source and phosphoric acid are added according to a V:P molar ratio of 0.95-1.05, and the mass of the carbon source is 20-50%wt of the vanadium metal amount (in terms of V2O5), preferably 20-35%wt; water is added to control the vanadium concentration in the solution to 0.5-10mol / L, preferably 1-6mol / L.
[0014] Furthermore, the vanadium source in step 1 is one or more of ammonium metavanadate, ammonium polyvanadate, V2O5, V2O4 and vanadyl oxalate.
[0015] Furthermore, the carbon source in step 1 is one or more of citric acid, oxalic acid, glucose, sucrose, starch and diatomaceous acid.
[0016] Furthermore, the lithium source in step 2 is one or more of lithium phosphate, lithium carbonate, lithium hydroxide, lithium acetate, and lithium citrate.
[0017] Furthermore, the sodium source in step 2 is one or more of trisodium phosphate, disodium hydrogen phosphate, sodium carbonate, sodium hydroxide, sodium diatomate, etc.
[0018] When only a lithium source is added in step 2, a LVP precursor is obtained in step 2. When only a sodium source is added, a NVP precursor is obtained in step 2. When both a lithium source and a sodium source are added, a mixture of a LVP precursor and a NVP precursor is obtained.
[0019] Furthermore, the drying temperature in step 2 is 80-140° C., and the drying time is 2-6 hours.
[0020] Furthermore, the inert atmosphere in step 3 is one or more of nitrogen or argon.
[0021] Furthermore, in step 3, the calcination temperature is 300-600° C., and the calcination time is 6-8 hours. Preferably, the calcination temperature is 400-600° C., and the calcination time is 6-7 hours.
[0022] Furthermore, the carbon content in the amorphous porous pre-product in step 3 is ≤1%, preferably 0.5-1%. Unless otherwise specified, % in the present invention refers to mass percentage.
[0023] Further, the particle size D after wet grinding in step 4 50 Less than or equal to 1um, preferably 0.1-0.5μm.
[0024] Furthermore, in step 4, the mass ratio of the total mass of the secondary carbon composite raw material to vanadium pentoxide is 1-10%, preferably 5-10%.
[0025] Furthermore, the secondary carbon composite raw material in step 4 comprises organic carbon A, inorganic carbon B, and dispersed carbon source C in a mass ratio of 3-5:0-1:1-10, preferably in a mass ratio of 3-5:0-1:1-8, and more preferably in a mass ratio of 3-5:0.5-1:1-5.
[0026] Furthermore, the organic carbon A is a carbon source that can provide a uniform coating carbon layer, and the organic carbon A is one or more of maltodextrin, microcrystalline cellulose, starch, phenolic resin, asphalt, glucose and sucrose.
[0027] Furthermore, the inorganic carbon B is a carbon source that can improve the degree of graphitization and the electrical conductivity, and the inorganic carbon B is one or more of carbon dots CDs, carbon nanotubes, graphene, Ketjen black and conductive carbon black.
[0028] Furthermore, the dispersed carbon source C is a carbon source that can prevent aggregation between particles, improve dispersibility, and has a steric hindrance effect. The dispersed carbon source C is one or more of polypyrrolidone PVP, polyethylene glycol PEG, and polyvinyl alcohol PVA.
[0029] Furthermore, the drying in step 5 is flash evaporation or spray drying.
[0030] Furthermore, the drying temperature in step 5 is 100-150° C., and the drying time is 2-4 hours.
[0031] Furthermore, the calcination temperature in step 5 is higher than the calcination temperature in step 3. Under the premise of maintaining the activity and stability of the material by low-temperature sintering, increasing the temperature can further improve the densification and performance optimization of the material. The calcination temperature in step 5 is 750-950°C, and the calcination time is 3-15h. The preferred calcination temperature is 750-900°C, and the preferred calcination time is 6-10h.
[0032] Another object of the present invention is to disclose a modified NASICON structure vanadium phosphate composite material, which is prepared by the above method.
[0033] Furthermore, the modified NASICON structure vanadium phosphate composite material has uniform carbon coating, regular material morphology and particle size, and powder resistivity is ≤8Ω·cm (under 50Mpa).
[0034] Furthermore, the specific surface area of the modified NASICON structure vanadium phosphate composite material is 12-20 m 2 / g and tap density is 0.9-1.5g / cm 3 .
[0035] Another object of the present invention is to disclose a use of a modified NASICON structure vanadium phosphate composite material in the field of secondary batteries.
[0036] Furthermore, the modified NASICON structure vanadium phosphate composite material is particularly suitable for positive electrode materials of secondary batteries.
[0037] The present invention first prepares an amorphous porous pre-product with a trace amount of carbon (carbon content ≤ 1%) by a sol-gel method, modifies the carbon layer by adding a secondary carbon coating combination formula in a subsequent wet grinding process, and finally prepares a NASICON structure vanadium phosphate composite material with high electrochemical performance and good processing performance by high-temperature calcination. Specifically, the present invention has the following advantages compared with the prior art:
[0038] 1) The present invention adopts a special method for preparing an amorphous porous pre-product. This structure can not only improve the uniform dispersion of carbon components into the bulk phase during the subsequent high-temperature carbonization process, which is beneficial to the effective coating of carbon and the inhibition of local grain transition growth, but also the high-temperature firing of the amorphous pre-product can burn out a target phase crystal with obvious characteristic peaks, the material has better electrochemical properties, and it is easy to control to avoid over-firing and the appearance of impurities.
[0039] 2) The secondary carbon-coated composite raw material of the present invention can effectively improve the conductivity of the material and the carbon layer coating, so that the material has a lower specific surface area (12-20m2) at a lower carbon content (≤2%). 2 / g) and tap density (0.9-1.5g / cm 3 ), the material has good processing performance. Compared with the prior art, the carbon layer of the present invention is denser and can more effectively prevent the side reaction between the positive electrode material and the electrolyte and the dissolution of vanadium ions, thereby improving the stability and cycle performance of the material.
[0040] 3) The present invention adopts a method of grinding to control the particle size, and the special layer stacking structure of the pre-product is crushed and reorganized into spherical small particle agglomerates to further improve the material density. Compared with the prior art, the material of the present invention has a more uniform particle size and a more regular morphology, which is conducive to improving the processing performance and electrochemical performance of the material.
[0041] 4) The preparation method of the present invention is simple to operate and is suitable for large-scale industrial application. Compared with the prior art, the preparation method of the present invention has higher preparation efficiency and lower cost, which is conducive to popularization and application.
[0042] 5) The modified NASICON structure vanadium phosphate composite material of the present invention has low powder resistivity, good thermal stability and environmental friendliness, is suitable for preparing positive electrode materials, and has good application prospects and large-scale promotion potential in the field of secondary batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 This is a SEM image of a modified NASICON structure sodium vanadium phosphate positive electrode material prepared in Example 1 provided by the present invention;
[0044] Figure 2 This is a SEM image of a modified NASICON structure lithium vanadium phosphate positive electrode material prepared in Example 2 provided by the present invention;
[0045] Figure 3 This is a SEM image of a modified NASICON structure sodium vanadium phosphate positive electrode material prepared in Comparative Example 1 provided by the present invention;
[0046] Figure 4 This is a SEM image of a modified NASICON structure lithium vanadium phosphate positive electrode material prepared in Comparative Example 2 provided by the present invention;
[0047] Figure 5 A performance diagram of the charge and discharge curves of a sodium ion battery prepared from a modified NASICON structure sodium vanadium phosphate positive electrode material prepared in Example 1 of the present invention at 0.1C and 0.2C;
[0048] Figure 6 The performance diagram of the charge and discharge curves of a lithium-ion battery made from a modified NASICON structure lithium vanadium phosphate positive electrode material prepared in Example 2 of the present invention at 0.1C and 0.2C;
[0049] Figure 7 The performance diagram of the charge and discharge curves of a sodium ion battery prepared from a modified NASICON structure sodium vanadium phosphate positive electrode material prepared in Comparative Example 1 provided by the present invention at 0.1C and 0.2C;
[0050] Figure 8 The performance diagram of the charge and discharge curves of a lithium-ion battery prepared from a modified NASICON structure lithium vanadium phosphate positive electrode material prepared in Comparative Example 2 provided by the present invention at 0.1C and 0.2C;
[0051] Fig. 9 A cycle curve performance diagram of a sodium ion battery prepared from a modified NASICON structure sodium vanadium phosphate positive electrode material prepared in Example 1 and Comparative Example 1 of the present invention at 5C;
[0052] Fig.10 This is a cycle curve performance diagram of a lithium-ion battery made from a modified NASICON structure lithium vanadium phosphate positive electrode material prepared in Example 2 and Comparative Example 2 provided by the present invention at 5C. DETAILED DESCRIPTION
[0053] The present invention is further described below with reference to the examples. The description of the technical features described below is based on representative embodiments and specific examples of the present invention, but the present invention is not limited to these embodiments and specific examples. It should be noted that:
[0054] Unless otherwise stated, the units used in this specification are all international standard units, and the numerical values and numerical ranges appearing in the present invention should be understood to include the inevitable systematic errors in industrial production.
[0055] In this specification, the numerical range expressed using "a numerical value A to a numerical value B" means a range including the endpoints numerical values A and B.
[0056] In the present specification, a numerical range expressed using "above" or "below" means a numerical range including the number.
[0057] In this specification, the word "may" means both performing a certain process and not performing a certain process.
[0058] In this specification, the use of "optional" or "optional" indicates that certain substances, components, execution steps, application conditions and other factors are used or not used.
[0059] In this specification, when "normal temperature" or "room temperature" is used, the temperature may be 15-25°C.
[0060] In this manual, the reagents or instruments used without indicating the manufacturer are all conventional products that can be obtained through commercial purchase.
[0061] Example 1
[0062] This embodiment 1 discloses a method for preparing a modified NASICON structure sodium vanadium phosphate composite material:
[0063] 50 g of vanadium pentoxide and 15.19 g of glucose were weighed respectively, added to 300 g of water under stirring conditions, the solution temperature was raised to 85°C, and 53.88 g of phosphoric acid was added, and stirring was continued for 20 min for wet reaction; 45.02 g of trisodium phosphate was added under stirring conditions, the solution temperature was maintained at 90°C, the reaction was continued for 30 min, the solution gradually became viscous to a gel solid state, and was dried at 80°C for 4 h, and a precursor was obtained after grinding; the precursor was calcined at 500°C for 7 h under Ar atmosphere to obtain an amorphous porous pre-product; the pre-product was wet-ground, and 5 g of secondary carbon composite raw materials were added during the wet grinding process, including 1.96 g of glucose, 0.58 g of carbon nanotubes, and 2.46 g of polypyrrolidone PVP, and finally a uniform mixture was obtained, and the sand-ground slurry particle size D 50The mixture was spray dried at a temperature of 120°C for 3 hours, and the dried material was calcined at 850°C for 8 hours to obtain a modified NASICON structure sodium vanadium phosphate composite material.
[0064] like Figure 1 As shown, the modified NASICON structure sodium vanadium phosphate composite material prepared in this embodiment is a sphere, with good carbon coating and a layer of primary grains uniformly grown on the surface, the grain size is about 2μm, and the powder resistivity is measured at 50Mpa to be 4.5Ω·cm. The modified NASICON structure sodium vanadium phosphate composite material, conductive carbon black and binder are weighed in a ratio of 0.8:0.1:0.1, and the slurry is evenly coated on the positive electrode sheet, and assembled into a button battery in a glove box together with the sodium sheet, electrolyte and diaphragm. Figure 5 As shown, its first cycle efficiency is 97.22%, the discharge specific capacity can still reach 114 mAh / g at 0.2C, and the capacity retention rate after 500 cycles at 5C is 97%, showing good electrochemical performance.
[0065] Example 2
[0066] This Example 2 discloses a method for preparing a modified NASICON structure lithium vanadium phosphate composite material.
[0067] 64.4 g of vanadium tetroxide and 15 g of glucose were weighed respectively, added to 300 g of water under stirring conditions, the solution temperature was raised to 85°C, and 114.18 g of phosphoric acid was added, and stirring was continued for 20 min for wet reaction; 43.11 g of lithium carbonate was added under stirring conditions, the solution temperature was maintained at 90°C, the reaction lasted for 30 min, the solution gradually became viscous to a gel solid state, and was dried at 80°C for 4 h, and a precursor was obtained after grinding; the precursor was calcined at 500°C for 7 h under Ar atmosphere to obtain an amorphous porous pre-product; the pre-product was wet-ground, and 6.44 g of secondary carbon composite raw materials were added during the wet grinding process, including 2.52 g of glucose, 0.75 g of carbon nanotubes, and 3.17 g of polypyrrolidone PVP, and finally a uniform mixture was obtained, and the sand-ground slurry particle size D 50 The mixture was spray dried at a temperature of 120°C for 3 hours, and the dried material was calcined at 850°C for 8 hours to obtain a modified NASICON structure lithium vanadium phosphate composite material.
[0068] like Figure 2As shown, the modified NASICON structure lithium vanadium phosphate composite material prepared in this embodiment is also a sphere, with good carbon coating and a layer of primary grains uniformly grown on the surface, the grain size is about 200nm, and the powder resistivity is measured at 50Mpa to obtain a powder resistivity of 3Ω·cm. The modified NASICON structure lithium vanadium phosphate composite material, conductive carbon black and binder are weighed in a ratio of 0.8:0.1:0.1, and the mass ratio is mixed into a slurry, which is evenly coated on the positive electrode sheet, and assembled into a button battery in a glove box together with the lithium sheet, electrolyte and diaphragm. Figure 6 As shown, its first cycle efficiency is 97.26%, the discharge specific capacity can still reach 128mAh / g at 0.2C, and the capacity retention rate after 500 cycles at 5C is 99%, with good electrochemical performance.
[0069] Example 3
[0070] This embodiment 3 discloses a modified NASICON structure lithium vanadium phosphate / sodium composite material Li 2.8 Na 0.2 V2(PO4)3, the preparation method thereof is as follows:
[0071] 64.4 g of vanadium tetroxide and 15 g of glucose were weighed respectively, added to 300 g of water under stirring, the solution temperature was raised to 85°C, and 114.18 g of phosphoric acid was added, and stirring was continued for 20 min for wet reaction; 40.13 g of lithium carbonate and 4.11 g of sodium carbonate were added under stirring, the solution temperature was maintained at 90°C, the reaction lasted for 30 min, the solution gradually became viscous to a gel solid state, and was dried at 80°C for 4 h, and a precursor was obtained after grinding; the precursor was calcined at 500°C for 7 h under Ar atmosphere to obtain an amorphous porous pre-product; the pre-product was wet-ground, and 6.44 g of secondary carbon composite raw materials were added during the wet grinding process, including 2.52 g of glucose, 0.75 g of carbon nanotubes, and 3.17 g of polypyrrolidone PVP, and finally a uniform mixture was obtained, and the sand-ground slurry particle size D 50 The mixture was spray dried at a temperature of 120°C for 3 hours, and the dried material was calcined at 850°C for 8 hours to obtain a modified NASICON structure lithium vanadium phosphate / sodium composite material.
[0072] The prepared modified NASICON structure lithium vanadium phosphate / sodium composite material is also spherical, with good carbon coating and a layer of primary grains uniformly grown on the surface. The grain size is about 800nm, and the powder resistivity is measured at 50Mpa to be 8.3Ω·cm. The modified NASICON structure lithium vanadium phosphate / sodium composite material, conductive carbon black and binder are weighed in a ratio of 0.8:0.1:0.1, respectively, and the mass ratio is prepared into a slurry, which is evenly coated on the positive electrode sheet and assembled into a button battery in a glove box together with a lithium sheet, electrolyte and diaphragm. Its first cycle efficiency is 94.59%, the discharge specific capacity can still reach 105mAh / g at 0.2C, and the capacity retention rate after 500 cycles at 5C is 93%, showing good electrochemical performance.
[0073] Comparative Example 1
[0074] This comparative example 1 discloses a preparation method of a modified NASICON structure sodium vanadium phosphate composite material, which is basically the same as that of Example 1, except that in step (4), no secondary carbon composite raw material is added during the wet grinding of the pre-product.
[0075] 50 g of vanadium pentoxide and 15.19 g of glucose were weighed respectively, added to 300 g of water under stirring, the solution temperature was raised to 85 ° C, and 53.88 g of phosphoric acid was added, and the stirring was continued for 20 min for wet reaction; 45.02 g of trisodium phosphate was added under stirring, the solution temperature was maintained at 90 ° C, the reaction was continued for 30 min, the solution gradually became viscous to a gel solid state, and was dried at 80 ° C for 4 h, and a precursor was obtained after grinding; the precursor was calcined at 500 ° C for 7 h under Ar atmosphere to obtain an amorphous porous pre-product; the pre-product was wet-ground to obtain a uniformly mixed pre-product, and the sand-ground slurry particle size D was measured. 50 The material was spray dried at 120°C for 3 hours, and the dried material was calcined at 750°C for 6 hours to obtain a modified NASICON structure sodium vanadium phosphate composite material, such as Figure 3 As shown in the figure, although the morphology of this comparative example is also spherical, there are no primary particles on the surface of the sphere, indicating that the secondary carbon coating can control the generation of primary particles. The powder resistivity is measured to be 51Ω·cm. Figure 7 As shown, its first cycle efficiency is 90.46%, and the discharge capacity at 0.2C is 104mAh / g. Fig. 9 As shown, the capacity retention rate after 500 cycles at 5C is 80%, and the electrochemical performance is worse than that of Example 1.
[0076] Comparative Example 2
[0077] Comparative Example 2 discloses a preparation method of a modified NASICON structure lithium vanadium phosphate composite material, which is basically the same as that of Example 2, except that in step (4), no secondary carbon composite raw material is added during the wet grinding of the pre-product.
[0078] 64.4 g of vanadium tetroxide and 15 g of glucose were weighed respectively, added to 300 g of water under stirring, the solution temperature was raised to 85 ° C, and 114.18 g of phosphoric acid was added, and the stirring was continued for 20 min for wet reaction; 43.11 g of lithium carbonate was added under stirring, the solution temperature was maintained at 90 ° C, the reaction lasted for 30 min, the solution gradually became viscous to a gel solid state, and was dried at 80 ° C for 4 h, and a precursor was obtained after grinding; the precursor was calcined at 500 ° C for 7 h under Ar atmosphere to obtain an amorphous porous pre-product; the pre-product was wet-ground to obtain a uniformly mixed mixture, and the sand-ground slurry particle size D was measured. 50 The mixture was spray dried at 120°C for 3 hours, and the dried material was calcined at 850°C for 8 hours to obtain a modified NASICON structure lithium vanadium phosphate composite material. Figure 4 As shown, the modified NASICON structure lithium vanadium phosphate composite material prepared in this comparative example is a sphere, with no primary grains on the surface, and its powder resistivity is 35Ω·cm measured by powder resistivity at 50Mpa. The modified NASICON structure lithium vanadium phosphate composite material, conductive carbon black and binder are weighed in a ratio of 0.8:0.1:0.1, respectively, and the slurry is prepared in a mass ratio, evenly coated on the positive electrode sheet, and assembled into a button battery in a glove box together with the lithium sheet, electrolyte and diaphragm. Figure 8 As shown in the figure, its first cycle efficiency is 92.75%, and the discharge capacity at 0.2C can still reach 109mAh / g. Fig.10 As shown, the capacity retention rate after 500 cycles at 5C is 81%, and the electrochemical performance is worse than that of Example 2.
[0079] Comparative Example 3
[0080] This comparative example 3 discloses a modified NASICON structure lithium vanadium phosphate / sodium composite material Li 2.8 Na 0.2 The preparation method of V2(PO4)3 is basically the same as that of Example 3, except that in step (4), the secondary carbon composite raw material is not added during the wet grinding of the pre-product.
[0081] 64.4 g of vanadium tetroxide and 15 g of glucose were weighed respectively, added to 300 g of water under stirring, the solution temperature was raised to 85°C, and 114.18 g of phosphoric acid was added, and stirring was continued for 20 min for wet reaction; 40.13 g of lithium carbonate and 4.11 g of sodium carbonate were added under stirring, the solution temperature was kept at 90°C, the reaction lasted for 30 min, the solution gradually became viscous to a gel solid state, and dried at 80°C for 4 h, and a precursor was obtained after grinding; the precursor was calcined at 500°C for 7 h under Ar atmosphere to obtain an amorphous porous pre-product; the pre-product was wet-ground to obtain a uniformly mixed mixture, and the sand-ground slurry particle size D 50 The mixture was spray dried at 120°C for 3 hours, and the dried material was calcined at 850°C for 8 hours to obtain a modified NASICON structure lithium vanadium phosphate / sodium composite material.
[0082] The prepared modified NASICON structure lithium vanadium phosphate / sodium composite material is also spherical, and its powder resistivity is 28Ω·cm when measured by powder resistivity at 50Mpa. The modified NASICON structure lithium vanadium phosphate / sodium composite material, conductive carbon black and binder are weighed in a ratio of 0.8:0.1:0.1, respectively, and the mass ratio is prepared into a slurry, which is evenly coated on the positive electrode sheet, and assembled into a button battery in a glove box together with a lithium sheet, an electrolyte and a diaphragm. Its first cycle efficiency is 91.28%, the discharge specific capacity can still reach 100mAh / g at 0.2C, and the capacity retention rate after 500 cycles at 5C is 75%. The electrochemical performance is worse than that of Example 3.
[0083] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a modified NASICON structure vanadium phosphate composite material, characterized in that: The following steps are involved: Step 1, adding a vanadium source and a carbon source into water under stirring conditions, then raising the temperature of the solution to 85°C-95°C, adding a phosphorus source, and continuously stirring for 10-30 minutes for wet reaction to obtain a suspension; Step 2: According to the molecular formula Li x Na 3-x V2(PO4)3, wherein 0≤x≤3, adding a lithium source and / or a sodium source under stirring conditions, reacting at 85-98°C for 10-60min, drying and grinding to obtain a precursor; Step 3, calcining the precursor under an inert atmosphere to obtain an amorphous porous pre-product; Step 4, wet grinding the amorphous porous pre-product, adding a secondary carbon composite raw material during the wet grinding process to obtain a uniform mixture; Step 5: Dry the mixture and calcine it to obtain a modified NASICON structure vanadium phosphate composite material.
2. The method for preparing the modified NASICON structure vanadium phosphate composite material according to claim 1, characterized in that: Step 1: adding vanadium source and phosphoric acid according to the V:P molar ratio of 0.95-1.05, the mass of carbon source is 20-50%wt of the vanadium metal; adding water to control the vanadium concentration in the solution to 0.5-10 mol / L; And / or, the vanadium source is one or more of ammonium metavanadate, ammonium polyvanadate, V2O5, V2O4 and vanadyl oxalate; And / or, the carbon source is one or more of citric acid, oxalic acid, glucose, sucrose, starch and diatomaceous acid.
3. The method for preparing the modified NASICON structure vanadium phosphate composite material according to claim 1, characterized in that: The lithium source in step 2 is one or more of lithium phosphate, lithium carbonate, lithium hydroxide, lithium acetate, and lithium citrate; And / or, the sodium source is one or more of trisodium phosphate, disodium hydrogen phosphate, sodium carbonate, sodium hydroxide, sodium diatomate, etc.
4. The method for preparing the modified NASICON structure vanadium phosphate composite material according to claim 1, characterized in that: Step 3: The calcination temperature is 300-600°C and the calcination time is 6-8h.
5. The method for preparing the modified NASICON structure vanadium phosphate composite material according to claim 1, characterized in that: In step 4, the mass ratio of the total mass of the secondary carbon composite raw material to vanadium pentoxide is 0-10%.
6. The method for preparing the modified NASICON structure vanadium phosphate composite material according to claim 1, characterized in that: The secondary carbon composite raw material in step 4 comprises organic carbon A, inorganic carbon B, and dispersed carbon source C in a mass ratio of 3 to 5:0 to 1:1 to 10; The organic carbon A is one or more of maltodextrin, microcrystalline cellulose, starch, phenolic resin, asphalt, glucose and sucrose; The inorganic carbon B is one or more of carbon dots CDs, carbon nanotubes, graphene, Ketjen black and conductive carbon black; The dispersed carbon source C is one or more of polypyrrolidone PVP, polyethylene glycol PEG and polyvinyl alcohol PVA.
7. The method for preparing the modified NASICON structure vanadium phosphate composite material according to claim 1, characterized in that: The drying in step 5 is flash evaporation or spray drying. And / or, the drying temperature is 100-150° C., and the drying time is 2-4 hours. And / or, the calcination temperature is higher than the calcination temperature in step 3, the calcination temperature in step 5 is 750-950° C., and the calcination time is 3-15 hours.
8. A modified NASICON structure vanadium phosphate composite material according to any one of claims 1 to 7, characterized in that: It is prepared by the above method.
9. The modified NASICON structure vanadium phosphate composite material according to claim 8, characterized in that: Its specific surface area is 12-20m 2 / g, tap density is 0.9-1.5g / cm 3 .
10. Use of the modified NASICON structure vanadium phosphate composite material according to claim 8 or 9 in the field of secondary batteries.